Benign Metastasizing Leiomyoma Causing Severe Tricuspid Regurgitation and Heart Failure - Mohammad Jaber MD; Patricia Jean Winner MD; Rajagopal Krishnan MD; Richard Shu MD; Keerti M. Khandelwal MD; Shivang Shah MD (SAGE Publishing, 2023)
We present the case of a 51-year-old woman with severe tricuspid valve regurgitation due to aseptic tricuspid valve vegetation. She presented with bilateral lower extremity edema and a tricuspid valve vegetation was found on echocardiography. Initially, infectious and autoimmune causes of valve vegetation were considered; however, on biopsy, the mass was ultimately found to be a benign metastasizing leiomyoma (BML). Additional history revealed clinical features consistent with uterine leiomyomas, which metastasized to all leaflets the tricuspid valve, causing symptoms of heart failure. Benign metastasizing leiomyoma is rare itself, but when found, typically presents as asymptomatic pulmonary nodules. Mechanism of spread is unknown. Diagnosis is typically made long after a hysterectomy or fibroidectomy, but in our case, the BML was found prior to an actual fibroid diagnosis. By comparison, metastasis to the heart is extremely rare and has a higher potential for morbidity. Our patient required open heart surgery and tricuspid valve replacement for management of her symptoms, but her risk of further or recurrent metastasis going forward is unknown. Management strategy to prevent metastases in such cases of aggressive disease is not an established protocol and needs to be further studied.